Building Climate-Resilient Cities through Sustainable Development: Malang’s Regional Experience 2020–2025 - Fathoni, Irfan; Sunarsih; Ramadhani, Dyon Seno (PANGRIPTA, 2025)
The accelerating pace of urbanization and environmental degradation in Indonesian secondary cities has heightened the urgency of aligning sustainable development with climate resilience strategies. This study explores Malang City’s regional experience between 2020 and 2025, analyzing air quality trends, population growth, land-use change, and local policy responses to climate risks. Results show that despite modest progress such as the creation of 98 urban parks, 8 urban forests, expansion of urban farming in 57 neighborhoods, and community-based climate initiatives (ProKlim) the city continues to face critical challenges, including recurrent floods (211 cases in 2022 alone), persistent air pollution (PM2.5 levels exceeding WHO thresholds), and declining green open space. Comparative insights from Surabaya and Semarang demonstrate that stronger spatial planning enforcement, innovative adaptation technologies, and inclusive governance can significantly improve resilience outcomes. This research advances the literature on regional development by framing sustainable development as a human-centered process that safeguards ecological systems, enhances quality of life, and ensures equitable benefits across social groups. It further provides practical implications for policymakers, urban planners, and community stakeholders in designing climate-resilient cities.